Studies on the shielding properties of some Ghanaian hardwoods against x-rays - Charles, Daniel Frederick (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of Master of Science Degree in Nuclear Physics, 2000